GAGALNYA PEMINDAHAN IBU KOTA NEGARA DI INDONESIA ABAD KE-20 - Yusuf, Nur Fadilah (Historia, 2025)
The study of political cannot be separated from the scope of its study which leads to power and policy. On the one hand, study of political can also be seen in the case of planning the construction of the national capital. National capitals, like building a city, can characterize the ideology and mentality of the rulers, and it is not uncommon for cities to serve as political legitimacy and historical memorials. This article uses the critical historical method with the stages of heuristics, source criticism, interpretation and historiography. This research focuses on the forms of failure of the relocation of the national capital shown through historical events. Based on this research, there are findings that become the novelty of the article including: The Relocation of the Capital in the Dutch East Indies Period, the State Capital in the Soekarno and New Order Eras and its Development. The three findings show that there are similarities in the forms of failure that make Jakarta have the magic so that its status remains as the capital of the country. Through the forms of failure to relocate the national capital, the failure can be caused by errors in policy direction and decision-making that have an impact on state losses.